Aqueous Ammonium‐Ion Supercapacitors with Unprecedented Energy Density and Stability Enabled by Oxygen Vacancy‐Enriched MoO3@C. (8th December 2022) - Dai, Juguo; Qi, Xueqiang; Xia, Long; Xue, Qian; Luo, Lili; Wang, Xiaohong; Yang, Chunying; Li, Dongxu; Xie, Hongmei; Cabot, Andreu; Dai, Lizong; Xu, Yiting
Abstract: The use of non‐metal charge carriers such as ammonium (NH4 + ) in electrochemical energy storage devices offers advantages in terms of weight, element abundance, and compatibility with aqueous electrolytes. However, the development of suitable electrodes for such carriers lags behind other technologies. Herein, we present a high‐performance anode material for ammonium‐ion supercapacitors based on a MoO3 /carbon (MoO3 @C) composite. The NH4 + storage performance of such composites and their practical application prospects are evaluated both in a three‐electrode configuration and as symmetric supercapacitors. The optimized material reaches an unprecedented specific capacitance of 473 F·g −1 (158 mAh·g −1 ; 1592 mF·cm −2 ) at a current density of 1 A·g −1, and 92.7% capacitance retention after 5000 cycles in a three‐electrode set‐up. This outstanding performance is related to the presence of oxygen vacancies that enhance the composites' ionic/electronic transportation and electrochemical reaction site, while at the same time facilitating the formation of hydrogen bonds between NH4 + and the host material. Using the optimized composite, symmetric supercapacitors based on an (NH4 )2 SO4 gel electrolyte are fabricated and demonstrated to provide unmatched energy densities above 78 Wh·kg −1 at a power density of 929 W·kg −1 . Besides, such devices are characterized by extraordinary capacitance retention of 97.6% after 10, 000 cycles. Abstract : NH4 + is made of extremely abundant elements and has a lower molar mass (18 g mol −1 ) and a smaller hydrated radius (3.3 Å) than most metal ions. These characteristics and the formation of hydrogen bonds between the metal oxide and NH4 + facilitate fast diffusion kinetics and reversible reaction.